1993
DOI: 10.4315/0362-028x-56.6.474
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the Effects of pH and Lactic or Acetic Acid Concentration on the Kinetics of Listeria Monocytogenes Inactivation

Abstract: The effects of pH and lactic acid or acetic acid concentration on Listeria monocytogenes inactivation were studied in brain heart infusion broth using a three strain mixture. Combinations of lactic acid/sodium lactate and acetic acid/sodium acetate were used to achieve concentrations of 0.1, 0.5, 1.0, and 2,0 M in conjunction with pH values of 4.0, 5.0, 6.0, and 7.0. Cultures adjusted with HCl to pH 3.0 to 7.0 in 0.5 pH unit intervals were used as 0.0 M controls. Each pH/concentration combination was inoculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(83 citation statements)
references
References 40 publications
5
73
1
2
Order By: Relevance
“…These D values are very similar to those we reported previously for 7H9-OADC medium (pH 6.8)-grown M. paratuberculosis (37) but higher than those previously reported for other bacterial pathogens. Acid survival D values for Yersinia enterocolitica O:3 were from 0.4 to 0.6 days at test pH 4 (24), and D values reported for Listeria monocytogenes were 0.5, 1.2, and 3.6 days at test pH 4, 5, and 6, respectively (1).…”
Section: Discussionmentioning
confidence: 89%
“…These D values are very similar to those we reported previously for 7H9-OADC medium (pH 6.8)-grown M. paratuberculosis (37) but higher than those previously reported for other bacterial pathogens. Acid survival D values for Yersinia enterocolitica O:3 were from 0.4 to 0.6 days at test pH 4 (24), and D values reported for Listeria monocytogenes were 0.5, 1.2, and 3.6 days at test pH 4, 5, and 6, respectively (1).…”
Section: Discussionmentioning
confidence: 89%
“…Glass et al (13) reported that populations of L. monocytogenes exhibited a decrease of 0.6 log 10 CFU/g in cheese (pH 5.6 to 5.84, 2.3 to 2.6% salt) stored for 4 days at 30°C. However, Buchanan et al (2) published a D value for L. monocytogenes in brain heart infusion broth (pH 5.0, acidified with 50 mM acetic acid) of 1.2 days at 28°C. That means the organism should have exhibited a decrease of 4 log 10 CFU/ml in the brain heart infusion broth during 4 days of storage based on the D value reported by Buchanan et al, but a reduction of only 0.6 log 10 CFU/g was found in cheese.…”
Section: Vol 66 2000mentioning
confidence: 99%
“…A bacterial strain can produce different shapes of survival curves. Frequently, concave curves may become convex or sigmoidal when the intensity of the stress varies (6,7,10,19,24,38,45,47,48). The patterns of survival curves may also vary with the physiological state of the cells and are dependent on the phase of growth (exponential or stationary phase) and also on the conditions of adaptation before the stress (18,25,36).…”
mentioning
confidence: 99%